Structural development of poly(ethylene terephthalate) during uniaxial stretching above the glass-transition temperatura: study of the statistical influence of the stretching variables - Todorov, Lyudmil V. (2011)
In this article, we present an investigation of the structural development of poly(ethylene terephthalate) (PET) during uniaxial stretching above the glass-transition temperature; this followed a statistical design of experiment approach to determine the influence of the stretching variables on the structural development. Amorphous PET was submitted to a stretching program with variations in the stretching temperature, stretching rate, and stretching ratio. Stretched samples were rapidly quenched and characterized by wide-angle X-ray scattering, optical birefringence, and differential scanning calorimetry. The relevance and influence of the stretching variables on the obtained parameters (phase fraction, phase orientation, and thermal parameters) were analyzed. The strain-induced crystallinity was controlled by stretching temperature,stretching ratio and the interaction between them. Mesophase development was not dependant on the stretching temperature but on the interaction between the stretching rate and ratio. The molecular orientation was proportionally dependent on the stretching temperature, stretching ratio and their interaction.